What does it take to be a copula? - Dalmi, Gréte (Yearbook of the Poznan Linguistic Meeting, 2016)
This paper argues that copular sentences without an overt copular predicate do project a VP with a phonologically null head, hence so-called “verbless” copular sentences are illusory. Data from Standard Arabic, Spanish, Maltese, Russian, Jamaican Creole, Finnish and Hungarian copular sentences are used to support this claim. It is also claimed here that variation between the habitual property vs. ad hoc property interpretations (traditionally called the individual level vs. stage level distinction) of non-verbal predicates found in copular sentences is closely related to the choice of the copula in multiple BE-system languages. Whilst the current accounts explain this variation by introducing an abstract aspectual operator or an incorporated abstract preposition in the functional layer of the copular predicate, the present proposal derives these interpretive differences from the presence or absence of an OPalt alternative state operator, which can bind the temporal variable of non-verbal predicates in two ways. Negation and temporal adverbials show scope ambiguity in copular sentences. They either take scope over the whole proposition or only over the non-verbal predicate. Such interpretive differences are demonstrated in Russian and Hungarian in Section 4 of this paper, however, they are taken to be valid cross-linguistically. These amibiguities cannot be explained under the “verbless copular sentence” account but fall out naturally from the “zero copula” analysis. The “alternative state” approach can be extended to dream narratives and other non-veridical contexts, which serve as alternative triggers. The existing analyses have nothing to say about such contexts.